Factors that Determine the Level of Poverty in the Province East Nusa Tenggara - Adelia, Viola Bella; Wijaya, Riko Setya (MediaTrend, 2024)
The issue of poverty is still a global topic of conversation. Poverty is still related to limited employment opportunities, and someone who does not work is poor. Meanwhile, someone is categorized as poor if they do not have an inadequate level of education and health. The strategic problems in East Nusa Tenggara Province have similarities to the problems faced by the central government, namely the high poverty rate. As for solving problems other than development and equality in East Nusa Tenggara Province, for the central authorities, namely eradicating the problem of poverty in NTT Province, is a fundamental issue and has priority to be addressed. Therefore, to determine the percentage of poor people in East Nusa Tenggara Province, which is ranked third out of 10 provinces in eastern Indonesia, researchers used several factors such as Gross Regional Domestic Product (GRDP), increase in Human Resources such as education and workforce, and the number of residents. Researchers use quantitative panel data linear regression methods with the aim of finding out the factors that impact poverty. So that it will produce future policies to reduce the poverty rate in NTT Province.